Prospective study on cervical neoplasia IV. Presence of HPV antibodies - Vonka, V; Hamsíková, E; Kanka, J; Ludvíková, V; Sapp, M; Smahel, M (International journal of cancer, 1999)
Sera collected in the course of a prospective study carried out in Prague in 1975-1983 were assayed for the presence of human papillomavirus (HPV) antibodies. Women with cervical neoplasia proven by biopsy at enrollment possessed antibodies to peptides derived from E2, E4 and E7 proteins of HPV16 and to virus-like particles (VLPs) of HPV16, -18 and -33 significantly more frequently than matched controls. Women without cervical neoplasia at enrollment who developed the disease in the course of the study differed from matched controls by a higher prevalence of antibodies against VLPs of HPV16 and -18 but not against early antigens of HPV16. In 19 of the latter subjects, paired serum specimens were tested, the first samples having been taken at enrollment and the second at diagnosis. Development of the disease was associated with seroconversion from negativity to positivity to at least one HPV antigen in 11 (57.9%) women.
Keywords: biologické markery; protilátky virové; DNA-Binding Proteins; Biomarkers; onkogenní proteiny virové; Uterine Cervical Neoplasms; nádory děložního čípku; Papillomavirus E7 Proteins; Adult; Prospective Studies; dospělí; DNA vazebné proteiny; lidé; ženské pohlaví; Papillomaviridae; Humans; Antibodies, Viral; Papillomavirus E7 - proteiny; Female; lidé středního věku; Oncogene Proteins, Viral; Middle Aged; prospektivní studie